The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/nmat4335
|View full text |Cite
|
Sign up to set email alerts
|

Potential-dependent dynamic fracture of nanoporous gold

Abstract: When metallic alloys are exposed to a corrosive environment, porous nanoscale morphologies spontaneously form that can adversely affect the mechanical integrity of engineered structures. This form of stress-corrosion cracking is responsible for the well-known 'season cracking' of brass and stainless steel components in nuclear power generating stations. One explanation for this is that a high-speed crack is nucleated within the porous layer, which subsequently injects into non-porous parent-phase material. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…The observation indicates that the surface plays a vital role in controlling the flow stress and, thereby, the strength in nanoscale plasticity. The recent reports from the groups of Jin on electrochemically controlled creep rate [20] and of K. Sieradzki on the impact of adsorbate coverage on fracture toughness [24] of NPG further emphasize this finding. Modulating the surface behavior electrochemically therefore provides new opportunities, as yet to be exploited in depth, for exploring the mechanisms that govern small-scale mechanical behavior.…”
Section: Role Of Surface Statementioning
confidence: 77%
See 1 more Smart Citation
“…The observation indicates that the surface plays a vital role in controlling the flow stress and, thereby, the strength in nanoscale plasticity. The recent reports from the groups of Jin on electrochemically controlled creep rate [20] and of K. Sieradzki on the impact of adsorbate coverage on fracture toughness [24] of NPG further emphasize this finding. Modulating the surface behavior electrochemically therefore provides new opportunities, as yet to be exploited in depth, for exploring the mechanisms that govern small-scale mechanical behavior.…”
Section: Role Of Surface Statementioning
confidence: 77%
“…After initial studies of NPG used small-scale testing schemes, [2,[12][13][14][15][16][17][18] it is now possible to make cm-size samples that can be subjected conventional macroscopic compression [7,11,[19][20][21][22] or even tension [11,23,24] tests. The large strain that is reached in compression affords testing protocols comprising, for example, strainrate jumps [7] or load-unload segments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that nanoporous gold can support cracking at a velocity of 200 m/s, which is about 50% of the limiting crack velocity in this material (i.e., the Rayleigh wave velocity). 10 Our current understanding of ambienttemperature electrochemical dealloying of alloys such as Ag-Au, Cu-Au, and Ni-Pt is based on the notion that connected preexisting atomicscale paths of the more electrochemically reactive component (Ag in the case of Ag-Au alloys) must exist in the alloy for selective dissolution to occur to depths greater than a few tens of nanometers. [11][12][13] Today, this general mechanism of dealloying is referred to as percolation dissolution.…”
Section: Dealloying-from Corrosion Science To the Physics Of Dealloyimentioning
confidence: 99%
“…(3), (13-16), (23) and (25). results (Balk et al, 2009;Lührs et al, 2016;Sun et al, 2015) and A was determined as a function of φ and ν E by numerically solving Eqs.…”
Section: Tablementioning
confidence: 99%